2016
DOI: 10.1016/j.rhm.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

“Girls need to behave like girls you know”: the complexities of applying a gender justice goal within sexuality education in South African schools

Abstract: Sexuality education, as a component within the Life Orientation (LO) programme in South African schools, is intended to provide young people with knowledge and skills to make informed choices about their sexuality, their own health and that of others. Key to the programme are outcomes relating to power, power relations and gender. In this paper, we apply a critical gender lens to explore the ways in which the teaching of sexuality education engages with larger goals of gender justice. The paper draws from a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…On the other hand, boys typically perform duties largely outside the home and are not very restricted in their movements. This finding is similar to that of Ngabaza [ 40 ] who found that boys and girls are socialised to perform different roles, have different expectations from parents, aunties and the wider communities. The differences exhibited in their aspirations like the values girls attach to motherhood, marriage, care giving and admiration for formal-sector jobs like nursing and teaching are a significant part of long-term gender ideals [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, boys typically perform duties largely outside the home and are not very restricted in their movements. This finding is similar to that of Ngabaza [ 40 ] who found that boys and girls are socialised to perform different roles, have different expectations from parents, aunties and the wider communities. The differences exhibited in their aspirations like the values girls attach to motherhood, marriage, care giving and admiration for formal-sector jobs like nursing and teaching are a significant part of long-term gender ideals [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…Various aunties play a complementary role by ensuring that girls become well-versed in the socially “appropriate” feminine behaviours and roles. These include the “proper” ways of how a good girl should sit, prepare food, conduct herself, respect elders and so on [ 40 ]. On the other hand, boys typically perform duties largely outside the home and are not very restricted in their movements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a growing body of research on sexuality education in South African schools, has increasingly illuminated the way in which HIV and GBV have been deployed towards governmentality over young people with respect gender, sexuality and dominant moralities (arguably shaped by northern, western, middle class framings) (for examples, Bhana, Crewe and Aggleton, 2019; Shefer, Macleod and Baxen, 2015). The reproduction and rationalisation of gender binarisms are shown to be reinforced through the dominant narrative of danger, disease and damage, in which young women in particular are set up as solely responsible for their own and their male partners' well-being (Macleod, Moodley and Saville-Young, 2015;Ngabaza, Shefer and Macleod, 2016), and for ensuring the performance of 'respectable femininity' (Van Wyk, 2015). Notwithstanding the critique of the stereotypic picture of women as victims, the opposite research inclination is equally a problem.…”
Section: The Reproduction Of Raced Classed Heteronormativity and Normentioning
confidence: 99%
“…Similarly, research on sexuality education at school foregrounds the complex conditions that undermine an LGBTIQ+ affirmative context in schools, and sexuality education is shown to be a site of heteronormative regulation and discipline rather than a space for facilitating freedom and diversity (e.g. Francis, 2017; Macleod, 2009; Ngabaza et al, 2016). Studies in schools provide qualitative evidence of the silencing and marginalization of learners with non-conforming desires and practices (Bhana, 2014a, 2014b; Francis, 2012; Msibi, 2012; Mthatyana and Vincent, 2015; Ngabaza et al, 2016).…”
Section: Introduction: Paradoxes Of Freedom and Injustice In A Human mentioning
confidence: 99%